(untitled) (Asian-Australasian Journal of Food Safety and Security, 2020)
Mycotoxins are agricultural contaminants of fungal origin occurring at all latitudes worldwide and being characterized by acute and chronic effects on human health and animal wellness, depending on the species sensitivity. Various types of crops like maize, wheat, soybeans etc are used as raw materials for preparing feed of fish and shrimp. They are particularly susceptible to infection by Aspergillus following prolonged exposure to a high humidity environment. For this reason, the fish and shrimp samples should be tested for identifying and quantifying mycotoxin. The major mycotoxins of food concern are aflatoxin (B1, B2, G1, G2) for its toxicity. This paper focus on the confirmation of aflatoxin in fish and shrimp by developing method and validated it by LC/MS-MS (ZEVO TQD) which is important for ensuring the safety of fishery product for human consumption. The monitored MRM transitions for B1, B2, G1, G2 were m/z 31357 and m/z 31371, m/z 31888 and m/z 318256, m/z 328.75242.99 and m/z 328.75199.9, m/z 330.3488 and m/z 330.34106 respectively. Limit of decision (CCα) for B1, B2, G1, G2 were 0.59 μg/kg, 0.70 μg/kg, 0.68 μg/kg, 0.83 μg/kg respectively and detection capability (CCβ) for B1, B2, G1, G2 were 1.01μg/kg, 1.19 μg/kg, 1.15 μg/kg, 1.40 μg/kg respectively. Asian Australas. J. Food Saf. Secur. 2020, 4 (1), 14-21